2016
DOI: 10.1007/978-3-319-30139-6_24
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Online Algorithms for the Multi-objective Time Series Search Problem

Abstract: Tiedemann, et al. [Proc. of WALCOM, LNCS 8973, 2015, pp.210-221] defined multiobjective online problems and the competitive analysis for multi-objective online problems, and showed best possible online algorithms with respect to several measures of the competitive analysis. In this paper, we first point out that the definitions and frameworks of the competitive analysis due to Tiedemann, et al. do not necessarily capture the efficiency of online algorithms for multi-objective online problems and provide modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…As we have mentioned, Hasegawa and Itoh [5] derived a closed formula of the arithmetic mean component competitive ratio for k = 2. In this section, we derive a closed formula of the arithmetic mean component competitive ratio for k = 2 given in Eq.…”
Section: Competitive Ratio For K =mentioning
confidence: 95%
See 3 more Smart Citations
“…As we have mentioned, Hasegawa and Itoh [5] derived a closed formula of the arithmetic mean component competitive ratio for k = 2. In this section, we derive a closed formula of the arithmetic mean component competitive ratio for k = 2 given in Eq.…”
Section: Competitive Ratio For K =mentioning
confidence: 95%
“…Without loss of generality, assume that Tiedemann,et al [10] presented best possible online algorithms for the multi-objective time series search problem with respect to the monotone functions f 1 , f 2 , and f 3 , i.e., the best possible online algorithm rpp-high for the multi-objective time series search problem with respect to the monotone function f 1 [10, Theorems 1 and 2], the best possible online algorithm rpp-mult for the bi-objective time series search problem with respect to the monotone function f 2 [10, Theorems 3 and 4] and the best possible online algorithm rpp-mult for the bi-objective time series search problem with respect to the monotone function f 3 [10, §3.2]. Recently, Hasegawa and Itoh [5] presented the deterministic online algorithm balanced price policy bpp and showed that bpp is best possible for any monotone function f : R k → R and for any integer k ≥ 2.…”
Section: Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in [2], a best possible algorithm for the bi-objective time series search problem is presented, as outlined below.…”
mentioning
confidence: 99%